THE ROLE OF INSTITUTIONAL SUPPORT IN FARMERS' WELFARE IN DENPASAR CITY - Ni Komang Indah Lestari Dewi; Ni Nyoman Reni Suasih (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study aims to analyze the influence of the role of government, farmers' groups, and subak institutions on farmers' welfare in Denpasar City, both simultaneously and partially. The research method employed is quantitative with an associative approach. The population of this study includes all active farmers who are members of farmers' groups and subak institutions in Denpasar City, while the sampling technique used is purposive sampling. Data were collected through questionnaires that had undergone validity and reliability testing, and were subsequently analyzed using multiple linear regression analysis. The results indicate that simultaneously, the roles of government, farmers' groups, and subak institutions significantly affect farmers’ welfare in Denpasar City. Partially, each of these three variables also has a positive and significant effect on farmers’ welfare. These findings underscore the importance of synergy between the government, farmers' groups, and traditional institutions such as subak in supporting the improvement of farmers' welfare in urban areas.